Tensile properties of geosynthetics after installation damage. Issue 3 (1st November 2013) - Pinho-Lopes, Margarida; Lopes, Maria de Lurdes
Abstract : In this paper, data from field installation trials of geosynthetics and laboratory tests are presented and analysed. The influence of several factors was assessed, namely nominal strength and type of geosynthetic, soil, compaction energy and method used to induce installation damage. Visual observations using a scanning electron microscope were performed. From the data collected, reduction factors for installation damage were derived using tensile strength values (traditional approach) and stiffness modulus (for 2% strain). Relative to the stiffness approach, the results obtained indicate that the traditional approach can be conservative. The reduction factors, determined using the traditional approach, were also compared with interval estimates from the literature. To contribute to supporting a shift from a factor of safety approach to a limit state design, bias statistics to correct the deterministic predictions were determined from the results. Different correlations were also established to enable using these results to interpolate reduction factors for similar installation conditions and/or geosynthetics from the same family of products. Installation damage reduction factors should be used in limit state design (ultimate and serviceability). Nevertheless, the stiffness approach can only be used for limit states where tensile failure of the geosynthetics will not occur.